Preoperative therapy of esophagogastric cancer: the problem of nonresponding patients - Blank, Susanne; Stange, Annika; Peters, Leila; Roth, Wilfried; Grenacher, Lars; Sterzing, Florian; Burian, Maria; Jäger, Dirk; Büchler, Markus W.; Ott, Katja (Langenbeck's archives of surgery, 2013)
Introduction Preoperative treatment is nowadays standard for locally advanced esophagogastric cancer in Europe. Surprisingly, little attention has been paid to nonresponders so far. The aim of our retrospective exploratory study was the comparison of responder, nonresponder, and primary resected patients in respect of outcome considering the tumor entity.Patients and methodsFrom 2001-2011, 607 patients with locally advanced esophagogastric carcinoma (adenocarcinoma of the esophagogastric junction (AEG), n = 293; squamous cell cancer (SCC), n = 111; gastric cancer, n = 203) after preoperative treatment (n = 281) or primary resection (n = 326) were included. Histopathological response evaluation (Becker criteria) was available for 263.Results A total of 76/263 (28.9 %) were responders (<10 % residual tumor). There was an association of response with increased R0 resections (p < 0.001) but also with a higher complication rate (p = 0.008) compared to nonresponse and primary surgery. Mortality was not influenced. Increased R0 resections after response were confirmed in every tumor entity (AEG, p = 0.010; SCC, p = 0.023; gastric cancer, p = 0.006). Median survival was best for responders with 43.5 months [95 % confidence interval (CI), 27.9-59.1], followed by nonresponders with 24.3 months (95 % CI, 21.6-27.0) and primary resected patients with 20.8 months (95 % CI, 17.7-23.9; p = 0.002). AEG (p = 0.012) and gastric cancer (p = 0.017) revealed identical results, but in the subgroup of SCC, the survival of nonresponders (median, 11.6 months; 95 % CI, 6.9-16.3) was even worse than for primary resected patients (median, 23.8 months; 95 % CI, 1.7-46.0; p = 0.012).ConclusionThe histopathological response rate was low. Generally, nonresponding patients with AEG or gastric cancer seem not to have a disadvantage compared to primary resected patients, but nonresponders with SCC have a worse prognosis, which strengthens the demand for a critical patient selection in surgery for this tumor entity.